Model Kinetika Pengeringan Ubi Jalar Ungu (Ipomoea batatas) Menggunakan Cabinet Dryer - Mukhlis, Andi Muhammad Akram; Sukainah, Andi; Putra, Reski Praja; Annisa, Khaerung (Agricultural Technology Education Study Program, 2024)
Sweet potato flour can also be used as a substitute ingredient in food manufacturing. Good control of the drying process is important to produce quality sweet potato flour. To understand the impact of drying on purple sweet potato, an in-depth understanding of drying kinetics is required. The equipment used in this research are cabinet dryer, analytical balance, electric oven, spatula, gegep, porcelain cup, desiccator, and aluminum cup. The material used in this study was fresh purple sweet potato obtained from Pasar Terong, Jl. Terong, Wajo Baru, Kec. Bontoala, Makassar City. Drying temperature became the treatment variable in this study. The temperature used consisted of 3 variations, namely 50oC, 55oC, and 60oC. Drying was carried out for 8 hours and measuring the moisture content every 1 hour during drying. The material moisture content (M) to be determined is the initial moisture content, final moisture content and material moisture content during the drying process. The moisture content of the material is determined using the oven method. Seven different drying mathematical models were evaluated. Determination of effective moisture diffusivity was carried out according to the Second Fick's Law Equation assuming the geometric shape of the material is slab. The drying rate showed a decreasing pattern along with the drying time of the material at various temperature variations. Based on the test results of the three statistical parameters, the Weibull Model has the highest correlation coefficient value.